Using Corticosteroids to Reshape the Gut Microbiome: Implications for Inflammatory Bowel Diseases. Issue 5 (May 2015) - Huang, Edmond Y.; Inoue, Takuya; Leone, Vanessa A.; Dalal, Sushila; Touw, Ketrija; Wang, Yunwei; Musch, Mark W.; Theriault, Betty; Higuchi, Kazuhide; Donovan, Sharon; Gilbert, Jack; Chang, Eugene B.
Abstract : Background: Commensal gut microbiota play an important role in regulating metabolic and inflammatory conditions. Reshaping intestinal microbiota through pharmacologic means may be a viable treatment option. We sought to delineate the functional characteristics of glucocorticoid-mediated alterations on gut microbiota and their subsequent repercussions on host mucin regulation and colonic inflammation. Methods: Adult male C57Bl/6 mice, germ-free, Muc2-heterozygote (±), or Muc2-knockout (−/−) were injected with dexamethasone, a synthetic glucocorticoid, for 4 weeks. Fecal samples were collected for gut microbiota analysis through 16S rRNA terminal restriction fragment length polymorphism and amplicon sequencing. Intestinal mucosa was collected for mucin gene expression studies. Germ-free mice were conventionalized with gut microbes from treated and nontreated groups to determine their functional capacities in recipient hosts. Results: Exposure to dexamethasone in wild-type mice led to substantial shifts in gut microbiota over a 4-week period. Furthermore, a significant downregulation of colonic Muc2 gene expression was observed after treatment. Muc2-knockout mice harbored a proinflammatory environment of gut microbes, characterized by the increase or decrease in prevalence of specific microbiota populations such as Clostridiales and Lactobacillaceae, respectively. This colitogenic phenotype was transmissible to IL10-knockout mice, a genetically susceptible model of colonic inflammatory disorders. Microbiota from donors pretreated with dexamethasone, however, ameliorated symptoms of inflammation. Conclusions: Commensal gut bacteria may be a key mediator of the anti-inflammatory effects observed in the large intestine after glucocorticoid exposure. These findings underscore the notion that intestinal microbes comprise a "microbial organ" essential for host physiology that can be targeted by therapeutic approaches to restore intestinal homeostasis. Abstract : Article first published online 3 March 2015.